2017
DOI: 10.5296/jas.v5i4.11991
|View full text |Cite
|
Sign up to set email alerts
|

Screening Camelia sinensis Germplasm Against Grey Leaf Blight of Tea

Abstract: Grey blight is a foliar disease of tea plants (Camellia sinensis) caused by Pestalotiopsis. The grey blight pathogen was isolated from infected leaves of tea plants in the National Tea and High Value Crop Research Institute (NTHRI), Shinkiari, Khyber Pakhtunkhwa, Pakistan. Eight different varieties, Indonesian, Roupi, Jue King, P-5, P-3, Qi man, Chuy and P-1, were investigated for yield loss and resistance against the grey blight disease. All varieties displayed considerably different levels of resistance to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Afterward, those samples were observed in laboratory by microbial culture media and microscopic analysis to compare causal pathogen to further ensure speci city of the predictions. For the rst sample, it was found that the leaf had been infected by Pestalotiopsis theae showing grey blight symptoms which is concordant with previous ndings [34]. Then the picture of the leaf was taken and checked by this proposed CNN model and the results of the model and laboratory test are similar.…”
Section: Simulation Environmentsupporting
confidence: 83%
“…Afterward, those samples were observed in laboratory by microbial culture media and microscopic analysis to compare causal pathogen to further ensure speci city of the predictions. For the rst sample, it was found that the leaf had been infected by Pestalotiopsis theae showing grey blight symptoms which is concordant with previous ndings [34]. Then the picture of the leaf was taken and checked by this proposed CNN model and the results of the model and laboratory test are similar.…”
Section: Simulation Environmentsupporting
confidence: 83%
“…On the other hand, experiment conducted by Kishor et al (2016) reported Trichoderma isolates' performance on effectively controlling this pathogen and concluded that integrated approach in pathogen management would be more fruitful if compatibility of BCA with fungicides were looked into. For long-term and environmentally friendly management of this disease, finding and deploying resistant varieties, specifically for organic tea production, is highly desirable (Akbar et al, 2017). Growers may be able to minimize infection by avoiding physical plant damage and by growing plants to avoid stress.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudopestalotiopsis camelliae-sinensis was shown to cause grey blight disease on tea plants in China [ 13 ]. Some research has showed that planting disease-resistant varieties of C. sinensis has a certain effect on controlling the tea plant disease infected by Pestalotiopsis species [ 14 ]. In addition, the Colletotrichum species is also a common group of plant pathogens that are responsible for anthracnose diseases [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%